Isotope-enabled large-eddy simulation outputs - Camille Risi; Caroline Muller; Peter Blossey (PANGAEA, 2020)
This dataset includes the outputs from 11 isotope-enabled large-eddy simulations. Simulations are done with the System for Atmospheric Modeling (SAM) non-hydrostatic model. The control simulation ("ctrl") is three-dimensional, with a doubly-periodic domain of 96 km x 96 km. The horizontal resolution is 750 m. There are 96 vertical levels. The simulation is run in radiative-convective equilibrium over an ocean surface with a sea surface temperature (SST) of 30°C. In two other simulations, the imposed SST is varied (26°C, 33°C): "26C" and "33C". In five other simulations, a large-scale vertical velocity forcing is imposed: - large-scale vertical velocity of -60hPa/d peaking at 500hPa: "omegaLSm60" - large-scale vertical velocity of -20hPa/d peaking at 500hPa: "omegaLSm20" - large-scale vertical velocity of +20hPa/d peaking at 500hPa: "omegaLS20" - large-scale vertical velocity of -60hPa/d peaking at 400hPa: "p400" - large-scale vertical velocity of -60hPa/d peaking at 600hPa: "p600" A simulation similar to "ctrl" is run with a horizontal resolution of 200m over a domain of 25.6 x 25.6km: "200m". Two simulations are similar to "ctrl" and "omegaLSm60" but without isotopic fractionation during rain evaporation: "ctrl_nofracrev" and "omegaLSm60_nofracrev". Outputs for simulations used in Risi et al 2020 include 1D variables and 3 variables in the lower troposphere. Outputs for simulations in Risi et al 2021 include 3D variables covering the full troposphere.